2004
DOI: 10.1370/afm.16
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Medical Errors by Family Physicians During Outpatient Visits

Abstract: BACKGROUND We wanted to describe errors and preventable adverse events identifi ed by family physicians during the offi ce-based clinical encounter and to determine the physicians' perception of patient harm resulting from these events. METHODWe sampled Cincinnati area family physicians representing different practice locations and demographics. After each clinical encounter, physicians completed a form identifying process errors and preventable adverse events. Brief interviews were held with physicians to asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 18 publications
(18 reference statements)
4
86
2
1
Order By: Relevance
“…24 All staff members were invited to anonymously report near-miss events using an online form that had been adapted from previous studies and field tested, with an average completion time of 2 minutes per report (See Appendix). 25 The online form did not include any patient identifiers, was available electronically from any Internet-enabled computer, and stored reports on a central computer in an encrypted format. Staff attended a standardized, 1-hour orientation and during the study period received an automated E-mail message every 2 weeks inviting them to report any near-miss event they could recall from the previous 2 weeks.…”
Section: Near-miss Reporting Systemmentioning
confidence: 99%
“…24 All staff members were invited to anonymously report near-miss events using an online form that had been adapted from previous studies and field tested, with an average completion time of 2 minutes per report (See Appendix). 25 The online form did not include any patient identifiers, was available electronically from any Internet-enabled computer, and stored reports on a central computer in an encrypted format. Staff attended a standardized, 1-hour orientation and during the study period received an automated E-mail message every 2 weeks inviting them to report any near-miss event they could recall from the previous 2 weeks.…”
Section: Near-miss Reporting Systemmentioning
confidence: 99%
“…(Batini & Scannapieco, 2016). However, supported by specialist literature (Banfield, et al, 2013;Elder, Meulen, & Cassedy, 2004), quality dimensions used in the evaluation phase of this thesis was informed by findings in Chapter 4 which concluded that accuracy and timeliness may lead to improved continuity of care. (ii) Meaningful but incorrect IS state from Wand and Wang (1996).…”
Section: Theoretical Approachmentioning
confidence: 96%
“…Reliability signifies that the data can be trusted to deliver correct information. Timeliness is defined by the delay between changes in the RW state and (Banfield, et al, 2013;Elder, Meulen, & Cassedy, 2004), quality dimensions used in the evaluation phase of this thesis was informed by findings in Chapter 4 which concluded that accuracy and timeliness may lead to improved continuity of care. …”
Section: Theoretical Approachmentioning
confidence: 99%
See 2 more Smart Citations